Optimization of Low-Fat Ice Cream Formulation using Response Surface Methodology (RSM) - Masrukan, Masrukan; Puspitasari, Anis Widi; SAR, Kuntjahjawati; Gorotomole, MM. Alamin (Journal Of Agritech Science (JASc), 2025)
This study aims to optimize the formulation of low-fat ice cream based on overrun and melting time. The study uses the Response Surface Methodology (RSM) combined with the Box-Behnken Design (BBD). The optimization of the ice cream formulation was conducted using variations in full cream milk (6.5, 8.5, and 10.5 g), baking powder (0.5, 1.25, and 2.0 g), and carrageenan (0.4, 0.7, and 1.0 g). The results of the ANOVA (Analysis of Variance) indicate that full cream milk and baking powder have a significant effect (p<0.05) on the overrun response, while carrageenan has a significant effect (p<0.05) on the ice cream melting time. Optimization to achieve the optimal overrun and melting time responses resulted in a formulation with 9.42 g of full cream milk, 2.0 g of baking powder, and 1.0 g of carrageenan. The ice cream from the optimal formulation has the following characteristics: total solids 34.76%, fat 3.03%, protein 2.90%, overrun 55.78%, and a melting time of 25.57 minutes.